2012
DOI: 10.1371/journal.pone.0032913
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Auditory Brainstem Response and Parental Bonding Style in Children with Gastrointestinal Symptoms

Abstract: BackgroundThe electrophysiological properties of the brain and influence of parental bonding in childhood irritable bowel syndrome (IBS) are unclear. We hypothesized that children with chronic gastrointestinal (GI) symptoms like IBS may show exaggerated brainstem auditory evoked potential (BAEP) responses and receive more inadequate parental bonding.Methodology/Principal FindingsChildren aged seven and their mothers (141 pairs) participated. BAEP was measured by summation of 1,000 waves of the electroencephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The predictive capacity of PIP with respect to anxiety and depression has been demonstrated, and these are the most common conditions in these caregivers. This is relevant because they can affect the quality of life and well-being of caregivers, can lead to other pathologies in the caregiver, can worsen their health [ 12 ], can deteriorate their children's adjustment to the disease [ 11 ] and, as a consequence of all of the above, can lead to increased health expenditure [ 1 3 ]. According to the World Health Organization (WHO), health is the interaction of multiple social, political, economic, cultural, and scientific factors, making this concept a complex reality that requires an interdisciplinary approach to address [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive capacity of PIP with respect to anxiety and depression has been demonstrated, and these are the most common conditions in these caregivers. This is relevant because they can affect the quality of life and well-being of caregivers, can lead to other pathologies in the caregiver, can worsen their health [ 12 ], can deteriorate their children's adjustment to the disease [ 11 ] and, as a consequence of all of the above, can lead to increased health expenditure [ 1 3 ]. According to the World Health Organization (WHO), health is the interaction of multiple social, political, economic, cultural, and scientific factors, making this concept a complex reality that requires an interdisciplinary approach to address [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to pay attention to the caregiver's adjustment to his or her child's diagnosis, as inappropriate parental behaviors have been observed to influence the patient's symptoms. [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The variability of genes that encode the proteins which play a pivotal role in regulating the HPA axis influence the inter-individual clinical response to antidepressants [26], [27]. Previous study from our laboratory reported that less maternal care and maternal overprotection form risk for IBS-like symptoms in 7-year old children [28]. Earlier studies have reported moderation of the effects of maltreatment on depression and neuroticism by a three-allele haplotype of CRH-R1 involving the single-nucleotide polymorphisms (SNPs) rs7209436 , rs110402 , and rs242924 [22], [23], [29].…”
Section: Introductionmentioning
confidence: 97%
“…In children, there is no direct evidence. Two studies reported that inadequate care by parents, which could be a proxy for insecure attachment, resulted in increased odds of FAPDs . Furthermore, children with FAPDs were more likely than their healthy peers to suffer from separation anxiety disorder which could be a sign of insecure attachment .…”
Section: Parent Psychological Factorsmentioning
confidence: 99%
“…Two studies reported that inadequate care by parents, which could be a proxy for insecure attachment, resulted in increased odds of FAPDs. 26,125 Furthermore, children with FAPDs were more likely than their healthy peers to suffer from separation anxiety disorder which could be a sign of insecure attachment. 14 However, the authors did find that family functioning (ranging from healthy to unhealthy and could be another proxy for attachment) did not differ between families with and without pain.…”
Section: Fapd and Attachmentmentioning
confidence: 99%